Application of hedonic dynamics using multiple-sip temporal-liking and facial expression for evaluation of a new beverage. (September 2016) - Rocha-Parra, Diego; García-Burgos, David; Munsch, Simone; Chirife, Jorge; Zamora, María Clara
Highlights: Hedonic dynamics and facial reactivity to taste for acceptance evaluation were used. Multiple sip methodology allowed observing changes in acceptance over the time. Men and women showed different hedonic response to a healthy beverage. Women showed greater negative valence score and higher disgust intensity. Abstract: Drinking and eating are not a matter of a single sip or bite. Dynamic data gathered from multiple sip or bite, seem to be more reliable than simple sip/bite evaluation. However, methodologies and analyses based on multiple sips/bites have received little attention until recently. The present study tested an innovative approach to measure the temporal changes in acceptance. It combines multiple-sip temporal-liking measurements (MSTL) with implicit taste reactivity using facial pattern expressions at different time points, for evaluation of a new beverage. Seventy-three consumers (35 females and 38 males) evaluated acceptance during 60 s, drinking three sips, with each sip every 20 s. The consumers' faces were filmed by a camera during the test session in order to analyze facial affective reactions. The results of the present paper show that MSTL modality allows seeing temporal changes in the acceptance of the beverage. Parameters analyzed maximum intensity (Imax ) and area under the curve (AUC) in self-reported response curves presented variation through successive sips. The self-rated liking increased from the first sip to the third. In the same way facial expressions also showed a change over time during successive sips. In this case, the basic emotion of disgust, unpleasantness-related Action Units (AUs; AU 26 and AU 15) and negative valence showed a decrease from the first sip to the third one. It was observed that negative facial reactions are greater than the positive facial reactions in intensity.